Ethnic Relations in Montenegro Twelve Years After Gaining Independence - Bešić, Miloš Lj. (Sociološki pregled, 2019)
This paper represents an analysis of inter-ethnic relations in Montenegro twelve years after this former Yugoslav republic gained its independence. Ethnic relations are analyzed using the method of ethnic distance measurement. We use empirical data to provide evidence of the level of inter-ethnic and overall ethnic distance in Montenegro. The research and measurement of ethnic distance is based on a traditional Bogardus social distance scale. Besides the descriptive task, the research goal of this paper is to show the effect of political factors on ethic distancing. We test this hypothesis using OLS regression analysis. We found a high level of inter-ethnic distance between Serbs on one side and minorities on the other. We also found a low level of ethnic distance between Montenegrins and Serbs, confirming that the clash between the two is political rather than ethnic by nature.
Keywords: Montenegro; ethnic relations; ethnic distance; Bogardus scale; OLS regression analysis